Diversity and ecological relationships of Cestoda and Monogenoidea parasites of freshwater stingrays (Myliobatiformes, Potamotrygonidae), in the upper Paraná River, Brazil - Chagas, Jumma Miranda Araújo [UNESP]; de Castro Ribeiro, Douglas [UNESP]; Mendes, Thalita Fischer Santini; Montefeltro, Felipe Chinaglia; dos Anjos, Luciano Alves (Elsevier, 2024)
The Neotropical freshwater stingrays of Potamotrygon genus present a unique and complex natural history and biogeographical pattern that can be traced to a marine origin and the colonization of the continental environment during the Miocene. During the evolution of potamotrygonids, several species of the parasitic fauna coevolved and co-opted concomitantly to their hosts during the colonization of the new environments. One striking example can be observed during the colonization of the upper Paraná River region. However, few studies explored the ecological and taxonomic aspects of potamotrygonid parasites. In this work, we investigate aspects of the ecology and taxonomy of the species of Monogenea and Cestoda that are parasites the species of freshwater stingrays of the genus Potamotrygon in the upper Paraná River. Our results indicate that at least six species of parasites are present in potamotrygonids in the region. Two of the observed parasites are putative new species and three of the parasitic species were identified for the first time in the region, hence expanding their geographic distributions. We quantified ecological aspects at different levels of communities for the collected parasite species. We compared the diversity in different locations and hosts and performed an exploratory analysis to investigate the differences in parasite abundance. Additionally, an identification key for the Monogenea and Cestoda species of the sampled region is provided.